PEMANFAATAN LIMBAH PLASTIK DAN SERBUK GERGAJI SENGON UNTUK PEMBUATAN PAPAN KOMPOSIT - Sushardi -; Eko Setyagama (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Recently, potential plastic garbage and sawdust increasing fastly. Disposal of plastic waste and sawdust in large numbers at random are very disturbing quality of the environment. Various attempts were made to utilize waste plastic waste and sawdust, one of which is the manufacture of plastic composites. The study aims to determine the optimal combination between the composition of plastic waste materials and sawdust kind Polyethylene sengon by using adhesive urea formaldehyde (UF) which can produce optimal quality composite board. The research design used is a factorial experiment with three (3) replicates arranged in a completely randomized design or a Completely Randomized Design (CRD), which consists of two factors, namely the composition of plastic waste materials and sawdust sengon (10%: 90% and 30 %: 70%), and the factor levels of gluten (7% and 8%) of the weight of air-dried material, with analyzed using SPSS. Parameters measured were moisture content, density and firmness press parallel to the surface. The results showed the composition of the material and content of the adhesive significantly affect the density and firmness press, while the water content only on the composition of the material. The average value of the water content of 6.461 to 9.977%, a density from 0.412 to 0.573 g / cm3, and firmness press parallel to the surface of 18.652 to 28.520 kg / cm2, in accordance with the standards dipersyaratkan.Limbah sengon plastic and sawdust can be used as a raw material composite board , the composition of materials that produce optimal products in this study using the composition of the waste material and plastic sawdust sengon 70%: 30%.Keywords: Waste plastic, sawdust sengon, composite board